1999
DOI: 10.1073/pnas.96.6.3211
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic effects of infection with a preproenkephalin-encoding herpes virus

Abstract: To test the utility of gene therapeutic approaches for the treatment of pain, a recombinant herpes simplex virus, type 1, has been engineered to contain the cDNA for an opioid peptide precursor, human preproenkephalin, under control of the human cytomegalovirus promoter. This virus and a similar recombinant containing the Escherichia coli lacZ gene were applied to the abraded skin of the dorsal hindpaw of mice. After infection, the presence of beta-galactosidase in neuronal cell bodies of the relevant spinal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 37 publications
12
152
3
2
Order By: Relevance
“…Thus, we tried a similar experiment, except that this time we tried pretreating the skin with capsaicinthe component of hot peppers that make them hot-to sensitize the nociceptors innervating the epidermis to heat stimulation. 1 Repeating the experiment, we found that the vector treatment produced a robust antihyperalgesia, reversing the sensitizing effects of capsaicin. These effects held up for at least 7 weeks after infection.…”
Section: Human Preproenkephalin Vectormentioning
confidence: 74%
“…Thus, we tried a similar experiment, except that this time we tried pretreating the skin with capsaicinthe component of hot peppers that make them hot-to sensitize the nociceptors innervating the epidermis to heat stimulation. 1 Repeating the experiment, we found that the vector treatment produced a robust antihyperalgesia, reversing the sensitizing effects of capsaicin. These effects held up for at least 7 weeks after infection.…”
Section: Human Preproenkephalin Vectormentioning
confidence: 74%
“…20,21 Equivalent findings for reduction of pain-related behaviors, tissue damage and decreased inflammation with use of similar HSV preproenkephalin overexpression vectors are reported for cutaneous and knee joint pain models. 20,22,53,54 Released enkephalins have been measured in the spinal cord and skin using the same HSV-preproenkephalin vector injected cutaneously in rats and monkeys. 26,54 It is known that enkephalin directly inhibits neurotransmitter release, including substance P, from presynaptic nerve terminals in both the central and peripheral nervous systems, 55 through a calcium channel blocking action.…”
Section: Anti-inflammatory Effects and Tissue Protection By Hsv-enk Tmentioning
confidence: 99%
“…Surexpression du gène de la proenképhaline A Une stratégie différente a été utilisée par deux autres groupes [6,7] pour surexprimer la pEnkA dans les neu-…”
Section: Thérapie Génique Expérimentale De La Douleurunclassified
“…Ces vecteurs permettent l'introduction du transgène dans les corps cellulaires des neurones sensoriels à la suite d'une infection périphérique. Chez des souris dont les neurones sensoriels ont été préalablement sensibilisés par des agents chimiques, mimant les conditions rencontrées dans les douleurs inflammatoires prolongées, la surexpression de la pEnkA humaine (sous contrôle du promoteur CMV) dans ces neurones atténue l'hyperalgésie consécutive à l'inflammation [6]. La même approche a montré un effet antinociceptif dans des modèles expéri-mentaux de douleur de type inflammatoire ou neuropa-…”
Section: Figure 1 Voies De Transmission Des Messages Douloureuxunclassified